Influence of dual-task constraints on the interaction between posture and movement during a lower limb pointing task - Silva, Marcelo Guimarães [UNESP] (2018)
One of the challenges regarding human motor control is making the movement fluid and at a limited cognitive cost. The coordination between posture and movement is a necessary requirement to perform daily life tasks. The present experiment investigated this interaction in 20 adult men, aged 18–30 years. The cognitive costs associated to postural and movement control when kicking towards a target was estimated using a dual-task paradigm (secondary auditory task). Results showed that addition of the attentional demanding cognitive task yielded a decreased kicking accuracy and an increased timing to perform the movement, mainly during the backswing motion. In addition, significant differences between conditions were found for COP and COM displacement (increased amplitude, mean speed) on the anteroposterior axis. However, no significant differences between conditions were found on the mediolateral axis. Finally, EMG analysis showed that dual-task condition modified the way anticipatory postural adjustments (APAs) were generated. More specifically, we observed an increase of the peroneus longus activity, whereas the temporal EMG showed a decrease of its latency with respect to movement onset. These results suggested a functional adaptation resulting in an invariance of overall APAs, emphasizing that cognitive, postural, and motor processes worked dependently.